Genes, Economics, and Happiness - Jan-Emmanuel De Neve; Nicholas A. Christakis; James H. Fowler; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Research on happiness has produced valuable insights into the sources of subjective well-being that are of importance to economics. A major nding from this literature is that people exhibit a "baseline" level of happiness that shows persistent strength over time. Here we explore the extent to which baseline happiness is in uenced by genetic variation. Using data from Add Health, we employ a twin study design to show that ge- netic variation explains about 33% of the variation in happiness, and that the in uence of genes varies by gender (women 26%, men 39%) and tends to rise with age. We also present evidence that variation in a specific gene predicts happiness. Individuals with a transcriptionally more eficient version of the serotonin transporter gene (SLC6A4) are significantly more likely to report higher levels of life satisfaction|having one or two alleles of the more eficient type raises the average likelihood of being very satis ed with one's life by 8.5% and 17.3%, respectively. Finally, using data from an indepen- dent source (the Framingham Heart Study) we show that a linked single nucleotide polymorphism (rs2020933) in the SLC6A4 gene also predicts life satisfaction. These results are the rst to identify a specific gene that may be associated with baseline levels of happiness.
Keywords: A12; Z00; 330; academia; Happiness; Subjective Well-Being; Genetics